'Internal relations' and Marx's 'materialist conception of history'. (February 2015) - Winslow, Ted
Relations are 'internal' where the 'essence' of the individual is the outcome of its relations. Marx's historical materialism treats social relations as internal in this sense. The human essence is the potential to develop the capabilities required for the actualisation of 'freedom' as activity objectifying universal intellectual, aesthetic and ethical values. Its full realisation requires the ideal social relations of 'communism'. Such relations are the end product of human history conceived as a dialectical process of internally related stages in which the development of individual capabilities is brought about by 'estrangement' within the internal production relations that define each stage.